Relationship between toe-heel length and body weight of newborn babies - Heru Pradjatmo, Heru Pradjatmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
Relationships between toe-heel length and body weight among newborn babies have been investigated. Five hundred and eighty eight infants were divided into two groups. The first group (training set) consisting of 293 cases was used to obtain the correlation between toe-heel length and body weight quantitatively defining mathematical functions (linear regression). Correlation coefficient was obtained by least squares method. The second group (test set) consisting of 295 cases was used to test whether the mathematical function could be generalized.Mathematical function describing the relationship between toe-heel length and body weight was Y= 77.854X - 2695.6 with correlation coefficient.r = 0.7887.Results of the test with the second group for estimating the body weight showed statistically no significant difference with the actual body weight (P > 0.05).Key words: toe-heel length - body weight - newborn babies - breech presentation - perinatal mortality